NF-kB’s contribution to B cell fate decisions - Guldenpfennig, Caitlyn; Teixeiro, Emma; Daniels, Mark (Frontiers in Immunology, 2023)
NF-κB signaling is essential to an effective innate and adaptive immune response. Many immune-specific functional and developmental outcomes depend in large on NF-κB. The formidable task of sorting out the mechanisms behind the regulation and outcome of NF-κB signaling remains an important area of immunology research. Here we briefly discuss the role of NF-κΒ in regulating cell fate decisions at various times in the path of B cell development, activation, and the generation of long-term humoral immunity.